Binder for dry coated electrodes
By using non-fibrillable adhesives prepared with fluoropolymers, the problems of environmental pollution and high energy consumption in the manufacture of dry electrodes of lithium-ion batteries are solved, and the preparation of high-performance electrodes is realized, which improves the mechanical integrity of the electrodes. and electrochemical stability.
Patent Information
- Application Number
- CN202380036939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-28
- Filing Date
- 2023-04-26
- Publication Date
- 2024-12-13
AI Technical Summary
In the manufacture of dry electrodes of existing lithium-ion batteries, organic solvents are required, which leads to environmental pollution and high energy consumption. Traditional adhesives are easily damaged at high temperatures, affecting the mechanical integrity and electrochemical stability of the electrodes.
Using a non-fibrillable adhesive composed of fluoropolymers with specific melting points and shear viscosity, it is used to prepare flexible self-supporting films, avoid additional shearing steps, reduce process energy consumption, and be treated by thermal machinery Improves the cohesion and adhesion of the electrodes.
The preparation of high-performance electrodes under solvent-free process conditions is achieved, which improves the mechanical integrity and electrochemical stability of the electrodes, reduces the adhesive ratio and heat treatment temperature, and improves the circulation capacity and energy density of the electrodes.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of electrical energy storage in lithium storage batteries (batteries) of the lithium ion type. More specifically, the present invention relates to a non-fibrillable (non-fibrillable, non-fibrillating) binder for dry-coated electrodes for lithium ion batteries. Another subject of the invention is a process for preparing electrodes using said binder. The present invention also relates to a lithium ion battery manufactured by incorporating said electrode. Background Art
[0002] The basic unit cell of a lithium-ion storage battery or lithium battery comprises an anode (when discharging) and a cathode (also when discharging), usually made of lithium insertion compounds of the metal oxide type, such as LiMn2O4, LiCoO2 or LiNiO2, between which is inserted an electrolyte that conducts lithium ions.
[0003] Rechargeable or secondary cells have advantages over non-rechargeable primary cells because the chemical reactions occurring at the positive and negative electrodes of the cell are reversible. The electrodes of a secondary cell can be regenerated many times by applying an electrical charge. Many advanced electrode systems have been developed to store charge. At the same time, a great deal of effort has been put into developing electrolytes that can improve the capabilities of electrochemical cells.
[0004] For its part, the electrodes generally comprise at least one current collector on which is deposited in the form of a film a composite material consisting of the so-called active material (because it is electrochemically active with respect to lithium), a polymer acting as a binder and one or more electronically conductive additives (usually carbon black or acetylene black) and optionally a surfactant.
[0005] Binders are classified as so-called inactive ingredients, as they do not directly increase the unit cell capacity. However, their crucial role in electrode processing and their significant influence on the electrochemical properties of the electrodes have been extensively described. The main relevant physical and chemical properties of binders include thermal stability, chemical and electrochemical stability, tensile strength (strong adhesion and cohesion), and flexibility. The main purpose of using binders is to form a stable network (cohesion) of the solid components of the electrode, i.e., active materials and conductive agents. In addition, the binder must ensure close contact (adhesion) between the composite electrode and the current collector.
[0006] Polyvinylidene fluoride (PVDF) is used as a binder in lithium-ion batteries due to its excellent electrochemical stability, good binding ability, and high adhesion to electrode materials and current collectors. PVDF can only be dissolved in certain organic solvents (such as N-methylpyrrolidone (NMP)), which are volatile, flammable, explosive and highly toxic, leading to serious environmental problems. In fact, in the wet slurry method, the active material and the binder are dispersed in a liquid solution. The liquid used is usually an organic solvent or water. The dispersion is cast on the current collector and then dried in a high-temperature oven to produce an electrode. In this process, a large amount of energy is required to dry the liquid component of the slurry, and the organic solvent also produces harmful vapors, which require special equipment to prevent free discharge into the environment.
[0007] Compared to conventional wet suspension electrode manufacturing methods, dry (solvent-free) manufacturing processes are simpler; these processes eliminate volatile organic compound emissions and offer the possibility of manufacturing electrodes with higher thickness (>120µm), ultimately resulting in energy storage devices with higher energy density. Changes in production technology have less impact on the active materials of the electrode, however, the polymer additives responsible for the mechanical integrity of the electrode must adapt to the new manufacturing conditions.
[0008] US 2019 / 0305316 discloses a dry electrode membrane, including a particulate non-fibrillable binder having a certain particle size, and a method for obtaining a membrane that is sufficiently flexible for a roll-to-roll process by using a fibrillable binder. However, the fibrillable binder requires additional shearing in addition to dispersing the components. This consumes high energy and causes damage to the active material. A dry electrode membrane including an elastic polymer binder is also known from US 2020 / 0313193, wherein the dry electrode membrane is self-supporting and contains at most a trace amount of polytetrafluoroethylene. US 2020 / 0313193 mainly discloses polyethylene as an elastic polymer binder, whose electrochemical stability is not sufficient for use in both the cathode and the anode of a lithium-ion secondary battery.
[0009] Therefore, there remains a need to develop new binders and electrode compositions for lithium-ion batteries that are suitable for processing without the use of organic solvents. Summary of the invention
[0010] According to a first aspect, the present invention provides a non-fibrillatable binder for dry-coated electrodes, the binder consisting of a fluoropolymer having a melting point between 145°C and 200°C measured according to ASTM D3418 and a melt viscosity below 50 kP measured at 230°C and a shear rate of 100 s-1 measured according to ASTM D3835.
[0011] In particular, the melting point is defined as the temperature at the peak of the melting endotherm measured according to ASTM D3418.
[0012] The present invention provides a binder with specific properties allowing the preparation of flexible self-supporting films. By using the fluoropolymer binder of the present invention, ductile electrode films can be obtained by mixing and dry electrode application in just one step.
[0013] The present invention also provides an adhesive that does not contain fibrillatable materials, so that an additional shearing step is avoided. As a result, the overall energy consumption of the process is lower than when a fibrillatable adhesive is used.
[0014] Furthermore, the fluoropolymer binders according to the present invention are more electrochemically stable than polyethylene, allowing electrochemical cells using such electrodes to have higher capacity and cycling properties.
[0015] According to a preferred embodiment, the fluoropolymer has a flexural modulus greater than 1000 MPa, measured according to ASTM D790.
[0016] According to a preferred embodiment, the fluorine-containing polymer comprises at least one fluorine-containing monomer selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2,3,3,3-tetrafluoropropylene, fluorinated vinyl ether, fluorinated allyl ether and fluorinated dioxole.
[0017] According to a preferred embodiment, the fluorine-containing polymer is selected from the group consisting of homopolymers of vinylidene fluoride and copolymers containing at least 50% by weight of vinylidene fluoride repeating units, and the comonomer is selected from the group consisting of chlorotrifluoroethylene, hexafluoropropylene and trifluoroethylene.
[0018] According to a preferred embodiment, the fluorine-containing polymer is a polyvinylidene fluoride (PVDF) homopolymer or a copolymer of vinylidene fluoride and hexafluoropropylene.
[0019] According to a preferred embodiment, the fluorine-containing polymer is a polyvinylidene fluoride homopolymer having head-to-tail defects in the vinylidene fluoride unit chain, and the degree of the head-to-tail defects does not exceed 10%.
[0020] According to a preferred embodiment, the fluoropolymer comprises functionalized monomers in an amount of 0.01 to 15 wt % based on the total monomers, preferably 0.05 to 5 wt % based on the total monomers, and even more preferably in an amount of 0.05 to 1.5 wt % based on the total monomers.
[0021] According to a preferred embodiment, the functionalized monomer having at least one functionality is selected from the group consisting of acrylic acid, methacrylic acid, vinylsulfonic acid, vinylphosphonic acid, itaconic acid, maleic acid and salts of such compounds; allyl glycidyl ether, methallyl glycidyl ether, crotonic acid glycidyl ether and acetic acid glycidyl ether; ethylene carbonate; hydroxyethyl acrylate and hydroxypropyl acrylate.
[0022] According to a preferred embodiment, the fluorine-containing polymer is prepared by emulsion polymerization or suspension polymerization, preferably emulsion polymerization.
[0023] According to a preferred embodiment, the fluoropolymer is a powder having a particle size distribution with a Dv50 of less than 20 μm, preferably less than 15 μm, in particular less than 10 μm.
[0024] Dv50 is the particle size at the 50th percentile (by volume) of the cumulative size distribution of the particles. This parameter can be determined by laser granulometry. This applies to all Dv50 mentioned in this specification. A Malvern INSITEC system particle size analyzer is used and the measurement is performed by dry approach on powders by laser diffraction with a focal length of 100 mm.
[0025] According to a second aspect, the present invention provides a dry-coated electrode comprising the non-fibrillable binder of the present invention, a conductive agent and a dry active material.
[0026] According to a preferred embodiment, the dry-coated electrode according to claim 8 has the following mass composition:
[0027] a. 50% to 99.9% active material, preferably 50% to 99%,
[0028] b. 0% to 25% of a conductive agent, preferably 0.5% to 25%,
[0029] c. 0.05% to 25% of a non-fibrillable binder, preferably 0.5% to 25%,
[0030] d. 0% to 5% of at least one additive selected from a plasticizer, an ionic liquid, a dispersant for a conductive additive and a flow aid;
[0031] The sum of all these percentages is 100%.
[0032] According to a preferred embodiment, the conductive agent comprises one or more materials selected from the group consisting of carbon black, such as acetylene black, Ketjen black; carbon fibers, such as carbon nanotubes, carbon nanofibers, vapor-grown carbon fibers; and metal powders, such as SUS powders and aluminum powders.
[0033] According to a preferred embodiment, for the positive electrode, the active material is selected from: LiCoO2, Li(Ni,Co,Al)O2, Li(1+x), NiaMnbCoc (x represents a real number of 0 or greater, a=0.8, 0.6, 0.5 or 1 / 3, b=0.1, 0.2, 0.3 or 1 / 3, c=0.1, 0.2 or 1 / 3), LiNiO2, LiMn2O4, LiCoMnO4, Li3NiMn3O3, Li3Fe2(PO4)3, Li3V2(PO4)3, lithium manganese spinel substituted with different elements, which has a composition represented by Li1+xMn2-x-yMyO4, wherein M represents at least one metal selected from Al, Mg, Co, Fe, Ni and Zn, and x and y independently represent a real number between 0 and 2; lithium titanate LixTiOy – x and y independently represent a real number between 0 and 2; and a lithium metal phosphate having a composition represented by LiMPO 4 , and M represents Fe, Mn, Co or Ni.
[0034] According to a preferred embodiment, for the negative electrode, the active material is selected from the group consisting of: lithium alloys, metal oxides, carbon materials such as graphite or hard carbon, silicon, silicon alloys and Li4TiO12.
[0035] According to a third aspect, the present invention provides a process for preparing a dry-coated electrode according to the present invention, the process comprising a thermomechanical treatment step carried out at a temperature ranging from 20°C below the melting point of the non-fibrillatable binder to up to 50°C above the melting point of the non-fibrillatable binder.
[0036] According to a fourth aspect, the present invention provides a lithium ion battery comprising a positive electrode, a negative electrode and a separator, wherein at least one electrode is a dry-coated electrode according to the present invention.
[0037] The invention allows to ensure the cohesion and mechanical integrity of the electrode, guaranteeing good film formation or consolidation of formulations that may be difficult to achieve for solvent-free processes; generating adhesion on the metal substrate; ensuring the uniformity of the electrode composition in thickness and width of the electrode; ensuring its uniformity in thickness and width of the electrode; reducing the total binder content in the electrode, which in known dry processes is still higher than in standard slurry processes. The advantages of this technology are to improve the following properties of the electrode: uniformity of the composition in thickness, cohesion and adhesion on the metal substrate. It also allows to reduce the binder ratio required in the electrode, as well as reducing the temperature and duration of the heat treatment required to improve adhesion. DETAILED DESCRIPTION
[0038] According to a first aspect of the present invention, there is provided a non-fibrillatable binder for a dry-coated electrode.
[0039] The term "fluoropolymer" means a polymer formed by polymerization of at least one fluorine-containing monomer, and includes homopolymers, copolymers, terpolymers, and higher polymers (which are thermoplastics). Fluoropolymers in certain embodiments of the present invention contain at least 50 mole percent of one or more fluorine-containing monomers in polymerized form.
[0040] "Thermoplastic" is understood herein to be a non-elastic polymer. An elastic polymer is defined as a polymer that can be stretched to twice its original length at ambient temperature and quickly recovers to within about 10% of its original length after release of the stress, as set forth by ASTM in Special Technical Publication, No. 184.
[0041] In a preferred embodiment, the binder consists of a fluoropolymer having a melting point measured according to ASTM D3418 of between 145°C and 200°C, preferably between 150°C and 195°C, more preferably between 150°C and 190°C, specifically between 150°C and 185°C, more specifically between 150°C and 180°C, especially between 150°C and 175°C, more especially between 150°C and 170°C, most especially between 150°C and 165°C, privilegedly between 150°C and 160°C.
[0042] In a preferred embodiment, the adhesive consists of a fluoropolymer having a melt viscosity of less than 50 kP measured at 230°C and a shear rate of 100 s-1, measured according to ASTM D3835. Advantageously, the fluoropolymer has a melt viscosity of less than 48 kP, preferably less than 46 kP, more preferably less than 44 kP, specifically less than 42 kP, more specifically less than 40 kP, measured at 230°C and a shear rate of 100 s-1, measured according to ASTM D3835.
[0043] Preferably, the fluoropolymer has a melt viscosity greater than 1 kP, preferably greater than 2 kP, particularly greater than 3 kP, specifically greater than 3.5 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
[0044] In a preferred embodiment, the binder consists of a fluoropolymer having a melting point measured according to ASTM D3418 of between 145°C and 200°C, preferably between 150°C and 195°C, more preferably between 150°C and 190°C, specifically between 150°C and 185°C, more specifically between 150°C and 180°C, specifically between 150°C and 175°C, more specifically between 150°C and 170°C, most specifically between 150°C and 165°C, privilegedly between 150°C and 160°C; and a melt viscosity measured according to ASTM D3835 at 230°C and a shear rate of 100 s-1 of less than 50 kP, advantageously less than 48 kP, preferably less than 46 kP, more preferably less than 44 kP, specifically less than 42 kP, more specifically less than 40 kP.
[0045] Thus, the binder consists of a fluoropolymer having a melting point measured according to ASTM D3418 of between 145°C and 200°C, preferably between 150°C and 195°C, more preferably between 150°C and 190°C, specifically between 150°C and 185°C, more specifically between 150°C and 180°C, specifically between 150°C and 175°C, more specifically between 150°C and 170°C, most specifically between 150°C and 165°C, privilegedly between 150°C and 160°C; and having a shear rate measured according to ASTM D3835 at 230°C and 100 s-1, lower than 50 kP, advantageously lower than 48 kP, preferably lower than 46 kP, more preferably lower than 44 kP, specifically lower than 42 kP, more specifically lower than 40 kP melt viscosity; and the fluoropolymer has a melt viscosity greater than 1 kP, preferably greater than 2 kP, more preferably greater than 3 kP, specifically greater than 3.5 kP measured at 230 ° C and a shear rate of 100 s-1 measured according to ASTM D3835.
[0046] In a preferred embodiment, the fluoropolymer has a flexural modulus greater than 1000 MPa measured according to ASTM D790. Advantageously, the fluoropolymer has a flexural modulus lower than 3000 MPa, preferably lower than 2900 MPa, more preferably lower than 2800 MPa, particularly lower than 2700 MPa, specifically lower than 2600 MPa, more specifically lower than 2500 MPa, measured according to ASTM D790.
[0047] Thus, the binder consists of a fluoropolymer having a melting point measured according to ASTM D3418 of between 145°C and 200°C, preferably between 150°C and 195°C, more preferably between 150°C and 190°C, specifically between 150°C and 185°C, more specifically between 150°C and 180°C, specifically between 150°C and 175°C, more specifically between 150°C and 170°C, most specifically between 150°C and 165°C, privilegedly between 150°C and 160°C; and having a shear rate measured according to ASTM D3835 at 230°C and 100 s-1, lower than 50 kP, advantageously lower than 48 kP, preferably lower than 46 kP, more preferably lower than 44 kP, specifically lower than 42 kP, more specifically lower than 40 kP; and the fluoropolymer has a flexural modulus greater than 1000 MPa measured in accordance with ASTM D790.
[0048] Preferably, the binder consists of a fluoropolymer having a melting point measured according to ASTM D3418 of between 145°C and 200°C, preferably between 150°C and 195°C, more preferably between 150°C and 190°C, in particular between 150°C and 185°C, more particularly between 150°C and 180°C, in particular between 150°C and 175°C, more particularly between 150°C and 170°C, most particularly between 150°C and 165°C, privilegedly between 150°C and 160°C; and having a shear rate measured according to ASTM D3835 at 230°C and 100 s-1, lower than 50 kP, advantageously lower than 48 kP, preferably lower than 46 kP, more preferably lower than 44 kP, in particular lower than 42 kP, more particularly lower than 40 and the fluoropolymer has a melt viscosity of greater than 1000 MPa measured according to ASTM D790 and a flexural modulus of less than 3000 MPa, preferably less than 2900 MPa, more preferably less than 2800 MPa, particularly less than 2700 MPa, specifically less than 2600 MPa, and more specifically less than 2500 MPa, measured according to ASTM D790.
[0049] In a more preferred embodiment, the fluoropolymer has a melting point measured according to ASTM D3418 between 145°C and 160°C, preferably between 150°C and 160°C. Alternatively, the fluoropolymer has a melting point measured according to ASTM D3418 between 160°C and 180°C.
[0050] In a more preferred embodiment, the fluoropolymer has a melt viscosity of between 1 and 10 kP, preferably between 2 and 10 kP, more preferably between 3 and 9 kP, measured at 230°C and a shear rate of 100 s-1, measured according to ASTM D3835. Alternatively, the fluoropolymer has a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1, measured according to ASTM D3835.
[0051] In a more preferred embodiment, the fluoropolymer has a flexural modulus measured according to ASTM D790 of between 1000 MPa and 1500 MPa, preferably between 1000 and 1400 MPa, more preferably between 1000 MPa and 1300 MPa. Alternatively, the fluoropolymer has a flexural modulus measured according to ASTM D790 of between 1300 and 3000 MPa, preferably between 1300 and 2750 MPa, more preferably between 1300 and 2500 MPa.
[0052] In the most preferred embodiment, the fluorine-containing polymer has
[0053] - a melting point between 145°C and 160°C, preferably between 150°C and 160°C, measured according to ASTM D3418,
[0054] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
[0055] In another most preferred embodiment, the fluorine-containing polymer, preferably polyvinylidene fluoride (PVDF) homopolymer, has
[0056] - a melting point between 160°C and 180°C as measured according to ASTM D3418,
[0057] - a melt viscosity of between 1 and 10 kP, preferably between 2 and 10 kP, more preferably between 3 and 9 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
[0058] In another most preferred embodiment, the fluorine-containing polymer, preferably polyvinylidene fluoride (PVDF) homopolymer, has
[0059] - a melting point between 160°C and 180°C as measured according to ASTM D3418,
[0060] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
[0061] In a particularly preferred embodiment, the fluorine-containing polymer has
[0062] - a melting point between 145°C and 160°C, preferably between 150°C and 160°C, measured according to ASTM D3418,
[0063] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835, and
[0064] - a flexural modulus measured according to ASTM D790 of between 1000 MPa and 1500 MPa, preferably between 1000 and 1400 MPa, more preferably between 1000 MPa and 1300 MPa.
[0065] In another particularly preferred embodiment, the fluorine-containing polymer, preferably a polyvinylidene fluoride (PVDF) homopolymer, has
[0066] - a melting point between 160°C and 180°C as measured according to ASTM D3418,
[0067] - a melt viscosity of between 1 and 10 kP, preferably between 2 and 10 kP, more preferably between 3 and 9 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835, and
[0068] - a flexural modulus measured according to ASTM D790 of between 1300 and 3000 MPa, preferably between 1300 and 2750 MPa, more preferably between 1300 and 2500 MPa, in particular between 1500 and 2500 MPa.
[0069] In another particularly preferred embodiment, the fluorine-containing polymer, preferably a polyvinylidene fluoride (PVDF) homopolymer, has
[0070] - a melting point between 160°C and 180°C as measured according to ASTM D3418,
[0071] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835, and
[0072] - a flexural modulus of between 1300 and 3000 MPa, preferably between 1300 and 2750 MPa, more preferably between 1300 and 2500 MPa, in particular between 1300 and 2000 MPa, measured according to ASTM D790.
[0073] In a preferred embodiment, the fluorine-containing polymer comprises at least one fluorine-containing monomer selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2,3,3,3-tetrafluoropropylene, fluorinated vinyl ether, fluorinated allyl ether and fluorinated dioxole.
[0074] Preferably, the fluorine-containing polymer comprises at least one fluorine-containing monomer selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene and fluorinated vinyl ether. In particular, the fluorine-containing polymer comprises at least vinylidene fluoride repeating units.
[0075] In a specific embodiment, the fluoropolymer is selected from the group consisting of homopolymers of vinylidene fluoride and copolymers containing at least 50% by weight of vinylidene fluoride repeating units, and the comonomer is selected from the group consisting of chlorotrifluoroethylene, hexafluoropropylene and trifluoroethylene. Particularly preferred copolymers are copolymers of vinylidene fluoride with hexafluoropropylene, hexafluoropropylene or chlorotrifluoroethylene, which contain from about 50% by weight to about 99% by weight of vinylidene fluoride, more preferably from about 70% by weight to about 99% by weight of vinylidene fluoride.
[0076] As used herein, the term "PVDF" includes homopolymers of vinylidene fluoride (VDF) or copolymers of VDF and at least one other comonomer, wherein the vinylidene fluoride comprises at least 50 weight percent.
[0077] In a preferred embodiment, the fluoropolymer is a polyvinylidene fluoride (PVDF) homopolymer or a copolymer of vinylidene fluoride and hexafluoropropylene. Preferably, the fluoropolymer is a polyvinylidene fluoride (PVDF) homopolymer or a copolymer of vinylidene fluoride and hexafluoropropylene, wherein the HFP content is less than or equal to 50 wt.%, advantageously less than or equal to 40 wt.%, preferably less than or equal to 30 wt.%, more preferably less than or equal to 20 wt.%, particularly less than 10 wt.%, and more particularly less than 8 wt.%. Therefore, the copolymer of vinylidene fluoride and hexafluoropropylene contains vinylidene fluoride repeating units and hexafluoropropylene repeating units.
[0078] Preferably, when the fluorine-containing polymer is a copolymer of vinylidene fluoride and hexafluoropropylene and the HFP content is less than or equal to 50 wt.%, advantageously less than or equal to 40 wt.%, preferably less than or equal to 30 wt.%, more preferably less than or equal to 20 wt.%, especially less than 10 wt.%; the fluorine-containing polymer has:
[0079] - a melting point between 145°C and 160°C, preferably between 150°C and 160°C, measured according to ASTM D3418,
[0080] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
[0081] More preferably, when the fluorine-containing polymer is a copolymer of vinylidene fluoride and hexafluoropropylene and the HFP content is less than or equal to 50 wt.%, advantageously less than or equal to 40 wt.%, preferably less than or equal to 30 wt.%, more preferably less than or equal to 20 wt.%, especially less than 10 wt.%; the fluorine-containing polymer has:
[0082] - a melting point between 145°C and 160°C, preferably between 150°C and 160°C, measured according to ASTM D3418,
[0083] - a melt viscosity of between 10 and 50 kP, preferably between 15 and 40 kP, more preferably between 20 and 40 kP, measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835, and
[0084] - a flexural modulus measured according to ASTM D790 of between 1000 MPa and 1500 MPa, preferably between 1000 and 1400 MPa, more preferably between 1000 MPa and 1300 MPa.
[0085] In a specific embodiment, the fluoropolymer is a polyvinylidene fluoride homopolymer or a copolymer of vinylidene fluoride and hexafluoropropylene, which has a head-to-tail defect in the vinylidene fluoride unit chain. The term "head-to-tail defect" refers to an inversion in the vinylidene fluoride unit chain. Preferably, the degree of head-to-tail defects does not exceed 10%. The degree of head-to-tail defects is determined by 19F-NMR measurement. Advantageously, the degree of head-to-tail defects does not exceed 9%, preferably does not exceed 8%, more preferably does not exceed 7%, especially does not exceed 6%, specifically does not exceed 5%, more specifically does not exceed 4%.
[0086] In another specific embodiment, the fluoropolymer is a copolymer of vinylidene fluoride and hexafluoropropylene, wherein the HFP content is less than or equal to 15 wt.%, advantageously less than or equal to 14 wt.%, preferably less than or equal to 13 wt.%, more preferably less than or equal to 12 wt.%, particularly less than 11 wt.%, more particularly less than 10 wt.%, most particularly less than 8 wt.%; and wherein the hexafluoropropylene repeating units are randomly distributed along the polyvinylidene fluoride main chain.
[0087] The fluoropolymer may further include monomers having at least one functional group selected from carboxyl, epoxy, carbonyl or hydroxyl. Examples of monomers capable of introducing carboxyl functional groups are unsaturated monoacids or unsaturated diacid monomers in free acid, salt or anhydride form, selected from sulfonic acid, phosphonic acid and carboxylic acid groups and their salts or anhydrides. Such monomers are acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphonic acid, itaconic acid, maleic acid and salts of such compounds. Examples of monomers capable of introducing epoxy functional groups are allyl glycidyl ether, methyl allyl glycidyl ether, crotonic acid glycidyl ether and acetate glycidyl ether. Examples of monomers capable of introducing carbonyl functional groups are ethylene carbonate. Examples of monomers capable of introducing hydroxyl functional groups are hydroxyethyl acrylate and hydroxypropyl acrylate.
[0088] The functionalized monomers may be used in an amount of 0.01% to 15% by weight based on the total monomers. Preferably, they are used in an amount of 0.05% to 5% by weight based on the total monomers, and even more preferably in an amount of 0.05% to 1.5% by weight based on the total monomers.
[0089] The functionalized fluoropolymers are primarily prepared by heterogeneous polymerizations, including suspension, emulsion, and microemulsion systems. Typically, each of these reactions requires at least one acid-functionalized monomer or salt thereof, at least one fluoromonomer, and a free radical initiator in an appropriate reaction medium. In addition, emulsion polymerizations of halogen-containing monomers typically require a surfactant capable of emulsifying both the reactants and the polymer product for the duration of the polymerization reaction.
[0090] According to one embodiment, the fluoropolymer used in the present invention is prepared by an emulsion polymerization process in the absence of a fluorinated surfactant.
[0091] In certain variations, the functionalized fluoropolymer used in the present invention may be prepared using a process similar to that disclosed in document WO 2012 / 030784. The temperature used for the polymerization may vary between 20 and 130° C. The pressure used for the polymerization may vary between 280 and 20,000 kPa.
[0092] Water, preferably deionized water, one or more functionalized monomers and at least one fluoromonomer are charged into a pressurized polymerization reactor equipped with an agitator and a thermal control device. The mixture may optionally contain one or more of a surfactant, a buffer, an antifouling agent or a chain transfer agent for molecular weight regulation of the polymer product. Before introducing one or more monomers, air is preferably removed from the reactor to obtain an oxygen-free environment for the polymerization reaction. The order of assembling the polymerization reaction components can vary, although it is generally preferred that at least a portion of the functionalized monomers are present in the aqueous reaction medium before the fluoromonomer polymerization begins. Additional amounts of functionalized monomers may be fed to the reactor during the reaction.
[0093] In one embodiment, water, initiator, functionalized monomer and optionally surfactant, antifoulant, chain transfer agent and / or buffer are loaded into the reactor, and the reactor is heated to the desired reaction temperature. Then (one or more) fluorinated monomers are fed into the reactor, preferably at a rate that provides a substantially constant pressure. Alternatively, fluorinated monomers, functionalized monomers and initiators can be fed into the reactor together with one or more of the optional ingredients. The monomer feed is terminated when the desired weight of monomer has been fed into the reactor. Optionally, additional free radical initiators are added, and the reaction is allowed to react for an appropriate amount of time. As the monomers in the reactor are consumed, the reactor pressure drops.
[0094] After the polymerization reaction is completed, the reactor is cooled to ambient temperature and the remaining unreacted monomers are discharged to atmospheric pressure. Subsequently, the aqueous reaction medium containing fluoropolymer is collected from the reactor as latex. The latex is composed of a stable mixture of reaction components, i.e., water, surfactant, initiator (and / or decomposition product of initiator) and functionalized fluoropolymer solids. The latex can contain about 10 wt % to about 50 wt %, preferably 20 wt % to 40 wt % polymer solids. The polymer in the latex is in the form of small particles, and the particle size range is from about 30 nm to about 800 nm.
[0095] After polymerization, the fluoropolymer is stirred, thickened and dried.
[0096] The fluoropolymer thus obtained is treated to form a powder. Fluoropolymer powders can be obtained by various processes. Powders can be obtained directly by emulsion or suspension synthesis processes by drying (by spray drying or by freeze drying). Powders can also be obtained by grinding techniques, such as cryo-grinding, in which the fluoropolymer is cooled to a temperature below room temperature before grinding, for example by liquid nitrogen.
[0097] In a preferred embodiment, the fluoropolymer is a powder having a particle size distribution with a Dv50 of less than 20 μm, preferably less than 15 μm, more preferably less than 10 μm. At the end of the powder manufacturing step, i.e. after the polymerization and drying steps, the particle size can be adjusted and optimized by selection or screening methods and / or by grinding when the Dv50 is greater than 10 μm. The particle size distribution referred to in this specification is usually obtained when the fluoropolymer is prepared by an emulsion process.
[0098] In another preferred embodiment, the fluoropolymer is prepared by a suspension process.
[0099] In a second aspect of the present invention, there is provided a dry-coated electrode comprising a non-fibrillable binder according to the present invention, a conductive agent and a dry active material.
[0100] In a preferred embodiment, the dry coated electrode has the following mass composition:
[0101] a. 50% to 99.9% active material, preferably 50% to 99%,
[0102] b. 0% to 25% of a conductive agent, preferably 0.5% to 25%,
[0103] c. 0.05% to 25% of a non-fibrillable binder, preferably 0.5% to 25%,
[0104] d. 0% to 5% of at least one additive selected from a plasticizer, an ionic liquid, a dispersant for a conductive additive and a flow aid;
[0105] The sum of all these percentages is 100%.
[0106] The conductive agent in the dry-coated electrode comprises one or more materials capable of improving conductivity. Some examples include carbon black such as acetylene black, Ketjen black; carbon fibers such as carbon nanotubes, carbon nanofibers, vapor-grown carbon fibers; metal powders such as SUS powders and aluminum powders.
[0107] Active materials are materials that are able to store and release lithium ions.
[0108] In a preferred embodiment, the electrode is a negative electrode. In particular, for the negative electrode, the active material is selected from: lithium alloys, metal oxides, carbon materials such as graphite or hard carbon, silicon, silicon alloys and Li4TiO12. The shape of the negative electrode active material is not particularly limited, but is preferably granular.
[0109] In another preferred embodiment, the electrode is a positive electrode. Preferably, for the positive electrode, the active material is selected from: LiCoO2, Li(Ni,Co,Al)O2, Li(1+x), NiaMnbCoc (x represents a real number of 0 or greater, a=0.8, 0.6, 0.5 or 1 / 3, b=0.1, 0.2, 0.3 or 1 / 3, c=0.1, 0.2 or 1 / 3), LiNiO2, LiMn2O4, LiCoMnO4, Li3NiMn3O3, Li3Fe2(PO4)3, Li3V2(PO4)3, lithium manganese spinel substituted with different elements, which has a composition represented by Li1+xMn2-x-yMyO4, wherein M represents at least one metal selected from Al, Mg, Co, Fe, Ni and Zn, and x and y independently represent real numbers between 0 and 2; lithium titanate LixTiOy – x and y independently represent a real number between 0 and 2; and a lithium metal phosphate having a composition represented by LiMPO 4 , and M represents Fe, Mn, Co or Ni.
[0110] In addition, the surface of each of the above materials may be coated. The coating material is not particularly limited as long as it has lithium ion conductivity and contains a material that can be maintained in the form of a coating on the surface of the active material. Examples of the coating material include LiNbO3, Li4Ti5O12, and Li3PO4.
[0111] The shape of the positive electrode active material is not particularly limited, but is preferably in a particle shape.
[0112] The present invention also relates to a process for preparing a dry coated electrode, said process comprising a thermomechanical treatment step carried out at a temperature ranging from 20°C below the melting point of the non-fibrillatable binder up to 50°C above the melting point of the non-fibrillatable binder.
[0113] The process for preparing the dry-coated electrode comprises the following steps:
[0114] - mixing the active material in powder form, the non-fibrillatable binder of the present invention and a conductive agent to prepare an electrode formulation;
[0115] - depositing the electrode formulation on a substrate by a solvent-free process to obtain a lithium-ion battery electrode; and
[0116] - Consolidating the electrode by thermomechanical treatment at a temperature ranging from 20°C below the melting point of the non-fibrillatable binder up to 50°C above the melting point of the non-fibrillatable binder.
[0117] The ingredients (the active material, the binder, the conductive agent, and optional additives) are mixed in powder form to prepare an electrode formulation.
[0118] The process for preparing the dry-coated electrode comprises the following steps:
[0119] - mixing the active material, the non-fibrillatable binder of the invention in powder form described above and a conductive agent using a process that provides an electrode formulation suitable for metal substrates by a "solventless" process;
[0120] - depositing the electrode formulation on a substrate by a solvent-free process to obtain a lithium-ion battery electrode; and
[0121] - Consolidating the electrode by thermomechanical treatment at a temperature ranging from 20°C below the melting point of the non-fibrillatable binder up to 50°C above the melting point of the non-fibrillatable binder.
[0122] A "solvent-free" process refers to a process that does not require a residual solvent evaporation step after the deposition step.
[0123] Thermomechanical treatment refers to a temperature between 20°C above the melting temperature of the polymer and up to 50°C above the melting temperature of the polymer applied with mechanical pressure. The pressure applied during the thermomechanical treatment is generally below 1 kN / mm, preferably below 0.75 kN / mm, more preferably below 0.5 kN / mm. Such thermomechanical treatment can be accomplished, for example, by a calender with heatable rollers or a plate-plate press which can also be heated.
[0124] According to one embodiment, after the powder mixing step, the electrode is manufactured as follows: by a solvent-free spray process, by depositing the formulation on a metal substrate, by a pneumatic spray process, by electrostatic spraying, by immersion in a fluidized powder bed, by sprinkling, by electrostatic screen printing, by deposition with a rotating brush, by deposition with a metering rotating roller, by calendaring.
[0125] According to one embodiment, after the powder mixing step, the electrode is manufactured in two steps by a solvent-free process. The first step comprises preparing a self-supporting film from a premixed formulation by a thermomechanical process such as extrusion, calendering or thermocompression. In the second step, the self-supporting film is laminated to a metal substrate by a process combining temperature and pressure such as calendering or thermocompression.
[0126] The mass ratio of the conductive agent to the active material is preferably 0% to 10%, more preferably 0% to 7%.
[0127] The mass ratio of the binder to the active material is preferably 0.1% to 10%, more preferably 0.5% to 7%.
[0128] According to one embodiment, the electrode components are all mixed at once according to conventional methods, resulting in an electrode formulation.
[0129] In one embodiment, the electrode formulation is applied to the substrate by electrostatic screen printing.Some examples of substrates are current collectors such as metal foils and metal meshes, polymer films, or solid electrolyte layers of solid-state batteries.
[0130] The preferred thickness of the electrode is 0.1 μm to 1000 μm, preferably 0.1 μm to 300 μm.
[0131] In a third aspect of the present invention, a lithium ion battery is provided. Preferably, the lithium ion battery comprises a positive electrode, a negative electrode and a separator, wherein at least one electrode is a dry-coated electrode according to the present invention.
[0132] Example:
[0133] The following examples illustrate the invention without limiting it.
[0134] Material:
[0135] PVDF 1: A homopolymer of vinylidene fluoride with a melting temperature of 165-172°C, a melt viscosity of 4-8 kP, and a flexural modulus of 1655-2310 MPa.
[0136] PVDF 2: A homopolymer of vinylidene fluoride with head-to-tail defects (5.5% defects) and a melting temperature of 161°C, a melt viscosity of 23.5-29.5 kP, and a flexural modulus of 1380-1790 MPa.
[0137] PVDF 3: A copolymer of vinylidene fluoride and hexafluoropropylene (about 5 wt% HFP) with about 1 wt% acrylic acid moieties having functional groups, characterized by a melting temperature of 151-157°C, a melt viscosity of 34-38 kP, and a flexural modulus of 1030 MPa.
[0138] PVDF 4: A copolymer of vinylidene fluoride and hexafluoropropylene (about 5 wt. % HFP - randomly distributed), characterized by a melting temperature of 155-160°C, a melt viscosity of 23-27 kP, and a flexural modulus of 1034-1241 MPa.
[0139] PVDF 5: A copolymer of vinylidene fluoride and hexafluoropropylene (about 12 wt % HFP) characterized by a melting temperature of 140-143°C, a melt viscosity of 12-20 kP, and a flexural modulus of 620-827 MPa.
[0140] PVDF 6: A copolymer of vinylidene fluoride and hexafluoropropylene (about 18 wt % HFP) characterized by a melting temperature of 117-125°C, a melt viscosity of 5-16 kP, and a flexural modulus of 192-276 MPa.
[0141] Electrode preparation
[0142] The negative electrode was prepared using each of the above PVDFs. 158-C (graphite, BTR) and a binder were added to a 125 ml plastic bottle with a lid. The ratio of 158-C to the binder was 98.5 / 1.5 (by weight). Zirconia beads were added to the container. The powder was mixed at 2000 rpm for 30 seconds by ARE-310 (Thinky). The mixed powder was sandwiched between two copper foils. The copper foil and powder were pressed in a roller press (SA-602, TESTER SANGYO CO., LTD.) at 160°C, 10 kN load, and 0.5 m / min speed. The prepared electrode was bent into a U shape and was considered qualified (OK) if no cracks or breakage occurred, and was considered unqualified (NOK) if cracks or breakage were found. The properties and results of each adhesive tested are shown in Table 1.
[0143] Table 1
[0144]
[0145] Melting point was measured according to ASTM D3418 / Melt viscosity was measured according to ASTM D3835 at 230°C and a shear rate of 100 s-1 / Flexural modulus was measured according to ASTM D790.
Claims
1. A non-fibrillatable binder for dry-coated electrodes, the binder consisting of a fluoropolymer having a melting point between 145°C and 200°C measured according to ASTM D3418 and a melt viscosity below 50 kP measured at 230°C and a shear rate of 100 s-1 according to ASTM D3835.
2. The adhesive of claim 1 wherein the fluoropolymer has a flexural modulus greater than 1000 MPa as measured according to ASTM D790.
3. The adhesive according to claim 1 or 2, wherein the fluorine-containing polymer comprises at least one fluorine-containing monomer selected from the group consisting of vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2,3,3,3-tetrafluoropropylene, fluorinated vinyl ether, fluorinated allyl ether, and fluorinated dioxole.
4. The adhesive according to any one of claims 1 to 3, wherein the fluorine-containing polymer is selected from: homopolymers of vinylidene fluoride and copolymers containing at least 50% by weight of vinylidene fluoride repeating units, and the comonomer is selected from chlorotrifluoroethylene, hexafluoropropylene and trifluoroethylene. 5 . The adhesive according to claim 1 , wherein the fluorine-containing polymer is a polyvinylidene fluoride (PVDF) homopolymer or a copolymer of vinylidene fluoride and hexafluoropropylene.
6. The adhesive according to any one of claims 1 to 5, wherein the fluorine-containing polymer is a polyvinylidene fluoride homopolymer having head-to-tail defects in the vinylidene fluoride unit chain, and the degree of the head-to-tail defects is not more than 10%.
7. The adhesive according to any one of claims 1 to 5, wherein the fluoropolymer comprises a functionalized monomer in an amount of 0.01 to 15 wt. % based on the total monomers, preferably 0.05 to 5 wt. % based on the total monomers, and even more preferably in an amount of 0.05 to 1.5 wt. % based on the total monomers.
8. The adhesive according to claim 6, wherein the functionalized monomer having at least one functional group is selected from: acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl phosphonic acid, itaconic acid, maleic acid and salts of such compounds; allyl glycidyl ether, methallyl glycidyl ether, crotonic acid glycidyl ether and acetate glycidyl ether; ethylene carbonate; hydroxyethyl acrylate and hydroxypropyl acrylate.
9. The adhesive according to any one of claims 1 to 8, wherein the fluorine-containing polymer is prepared by emulsion polymerization or suspension polymerization.
10. The adhesive according to any one of claims 1 to 9, wherein the fluoropolymer is a powder having a particle size distribution with a Dv50 of less than 20 μm, preferably less than 15 μm, in particular less than 10 μm, measured by laser granulometry.
11. A dry coated electrode comprising a non-fibrillatable binder according to any one of claims 1 to 10, a dry active material and optionally a conducting agent.
12. The dry coated electrode according to claim 11, having the following mass composition: a. 50% to 99.9% active material, preferably 50% to 99%, b. 0% to 25% of a conductive agent, preferably 0.5% to 25%, c. 0.05% to 25% of a non-fibrillable binder, preferably 0.5% to 25%, d. 0% to 5% of at least one additive selected from a plasticizer, an ionic liquid, a dispersant for a conductive additive and a flow aid; The sum of all these percentages is 100%.
13. The dry-coated electrode according to any one of claims 11 or 12, wherein the conductive agent comprises one or more materials from the following: carbon black, such as acetylene black, Ketjen black; carbon fiber, such as carbon nanotube, carbon nanofiber, vapor-grown carbon fiber; metal powder, such as SUS powder and aluminum powder.
14. The dry-coated electrode according to any one of claims 11 to 13, wherein for the positive electrode, the active material is selected from: LiCoO2, Li(Ni,Co,Al)O2, Li(1+x), NiaMnbCoc (x represents a real number of 0 or more, a=0.8, 0.6, 0.5 or 1 / 3, b=0.1, 0.2, 0.3 or 1 / 3, c=0.1, 0.2 or 1 / 3), LiNiO2, LiMn2O4, LiCoMnO4, Li3NiMn3O3, Li3Fe2(PO4)3, Li3V2(PO4)3, lithium manganese spinel substituted with different elements having a composition represented by Li1+xMn2-x-yMyO4, wherein M represents at least one metal selected from Al, Mg, Co, Fe, Ni and Zn, and x and y independently represent a real number between 0 and 2; lithium titanate LixTiOy- x and y independently represent a real number between 0 and 2; and a lithium metal phosphate having a composition represented by LiMPO 4 , and M represents Fe, Mn, Co or Ni.
15. A dry-coated electrode according to any one of claims 11 to 13, wherein for the negative electrode, the active material is selected from the group consisting of: lithium alloys, metal oxides, carbon materials such as graphite or hard carbon, silicon, silicon alloys and Li4TiO12.
16. Process for preparing a dry-coated electrode according to any one of claims 11 to 15, comprising a thermomechanical treatment step carried out at a temperature ranging from 20°C below the melting point of the non-fibrillatable binder up to 50°C above the melting point of the non-fibrillatable binder.
17. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, wherein at least one electrode is a dry-coated electrode according to any one of claims 11 to 15.
Citation Information
Patent Citations
Compositions and methods for dry electrode films including microparticulate non-fibrillizable binders
US20190305316A1
Compositions and methods for dry electrode films including elastic polymer binders
US20200313193A1
Method of producing fluoropolymers using acid-functionalized monomers
WO2012030784A1
